Feasibility of desensitizing children highly allergic to peanut by high‐dose oral immunotherapy. Issue 2 (8th October 2018) - Reier‐Nilsen, Tonje; Michelsen, Merethe Melbye; Lødrup Carlsen, Karin C.; Carlsen, Kai‐Håkon; Mowinckel, Petter; Nygaard, Unni C.; Namork, Ellen; Borres, Magnus P.; Håland, Geir
Abstract: Background: There are limited data on the feasibility, efficacy and safety of high‐dose oral immunotherapy (OIT) in children highly allergic to peanuts. Objective: In children highly allergic to peanut, we primarily aimed to determine the feasibility of reaching the maximum maintenance dose (MMD) of 5000 mg peanut protein or, alternatively, a lower individual maintenance dose (IMD), by OIT up‐dosing. Secondarily, we aimed to identify adverse events (AEs) and determine factors associated with reaching a maintenance dose. Methods: The TAKE‐AWAY peanut OIT trial enrolled 77 children 5‐15 years old, with a positive oral peanut challenge. Fifty‐seven were randomized to OIT with biweekly dose step‐up until reaching MMD or IMD and 20 to observation only. Demographic and biological characteristics, AEs, medication and protocol deviations were explored for associations with reaching maintenance dose. Results: All children had anaphylaxis defined by objective symptoms in minimum two organ systems during baseline challenge. The MMD was reached by 21.1%, while 54.4% reached an IMD of median (minimum, maximum) 2700 (250, 4000) mg peanut protein, whereas 24.5% discontinued OIT. During up‐dosing, 19.4% experienced anaphylaxis. Not reaching the MMD was caused by distaste for peanuts (66.7%), unacceptable AEs (26.7%) and social reasons (6.7%). Increased peanut s‐IgG4 /s‐IgE ratio (OR [95% CI]: 1.02 [1.00, 1.04]) was associated with reaching MMD. Conclusion: Although 75.5% of children with peanut anaphylaxis reached a maintenance dose of 0.25‐5 g, only 21.1% reached the MMD. Distaste for peanuts and AEs, including high risk of anaphylaxis, limited the feasibility of reaching MMD.